PENGARUH PEMBERIAN INSENTIF, MOTIVASI KERJA, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA ANGGOTA POLRI BIDANG GAKKUM PADA DIT POLAIR KORPOLAIRUD BAHARKAM POLRI - Rory Ratno Ardiansyah (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This case study aims to determine the effect of incentives, motivation, work discipline and organizational culture on employee performance. In this study there are four variables used, namely three independent variables and one dependent variable. Motivation, incentives and work culture variables are independent variables, while member performance variables are dependent variables. In processing this research data using the statistical program SPSS version 20.00 for windows. This study passed several statistical tests, namely Validity, Reliability and Hypothesis testing. Based on the results of the descriptive analysis described in the previous discussion, it can be concluded: In general there is an influence between the variables of motivation, incentives and organizational culture on member performance. In other words simultaneously there is the effect of variable X on variable Y or the relationship of variable X with significant variable Y. The amount of influence of motivation, incentives and work culture on the performance of members amounted to 97.7%.Partially, motivation and work culture variables affect employee performance and the magnitude of each of these variables is 63.4% and 21.9%. While the incentive variable does not affect member performance because it has a significance value of 0.194. Value of 0.194 is greater than 0.05%, meaning that it is not significant